2000
DOI: 10.1007/s001980070053
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Geometry of Human Finger Phalanges Using Quantitative Ultrasound In Vivo

Abstract: Quantitative Ultrasound (QUS) methods have been shown to be useful in the assessment of bone status. Nevertheless, ultrasound transmission depends on a variety of skeletal parameters, and a detailed understanding of ultrasound propagation through bone is important for the accurate interpretation of QUS results. In this study we wanted to elucidate the pathways of an ultrasound wave through finger phalanges and determine correlations between geometric and QUS parameters. Phalanges of a subject group were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 12 publications
(19 reference statements)
4
60
0
4
Order By: Relevance
“…The feasibility of in vivo quantitative ultrasound (QUS) measurements at the hip has been demonstrated, with a good clinical performance for hip fracture discrimination. (22,23) Interestingly-and similar to results previously obtained at the finger phalanges (24) -a thorough analysis of signals transmitted through the proximal femur suggested that different propagation pathways through the trabecular or cortical compartments could be identified, leading to the concept of multimodal QUS assessment of the proximal femur, by which both the trabecular and the cortical compartments could be assessed separately. Simulation studies of measurements at the proximal femur QUS (25) predicted the existence of a guided wave propagating circumferentially exclusively in the cortical shell of the neck.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…The feasibility of in vivo quantitative ultrasound (QUS) measurements at the hip has been demonstrated, with a good clinical performance for hip fracture discrimination. (22,23) Interestingly-and similar to results previously obtained at the finger phalanges (24) -a thorough analysis of signals transmitted through the proximal femur suggested that different propagation pathways through the trabecular or cortical compartments could be identified, leading to the concept of multimodal QUS assessment of the proximal femur, by which both the trabecular and the cortical compartments could be assessed separately. Simulation studies of measurements at the proximal femur QUS (25) predicted the existence of a guided wave propagating circumferentially exclusively in the cortical shell of the neck.…”
Section: Introductionsupporting
confidence: 70%
“…(26) Hence, variations of the time-of-flight (TOF) of this wave should reflect only the variations of geometric (size, cortical thickness), material (mass density, elasticity), and structural (porosity) properties of the cortical compartment. (24,27,28) The measurement of this guided wave is all the more interesting in that the strength of the FN has been associated to bone matrix mineral content, (29,30) cortical porosity, (31) and cortical thickness, (32,33) all of these properties contributing to the propagation characteristics of the guided circumferential waves. The issue of specifically measuring ultrasonically the cortical part of the proximal femur, however, has so far not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The positive correlation between bone size and ultrasound variables exists because body height influences the mechanical forces applied to the skeleton and subsequently bone strength. It seems, however, that QUS techniques-especially Ad-SoS-may be less affected by bone size than DXA measurements [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…However, it may not be appropriate for assessing a maturing skeleton, as it allows only two-dimensional measurements and depends on bone size, therefore making the results potentially inaccurate [10]. Measurements made by quantitative ultrasound (QUS) are less influenced by bone size [11][12][13]. Importantly, when considering the paediatric population, no radiation is used and costs are relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…Single-point QUS (DBM Sonic 1200; Igea, Carpi, Italy), originally developed for the evaluation of adult phalanges (25), provides not only SOS but also the bone transmission time (BTT, in ms) that is not affected by the thickness of the soft tissue (25). Moreover, a detailed evaluation of the ultrasound waves transmitted by this device has been described (26) and validated in vitro (27) as well as in the growing skeleton: single-point QUS assesses bone status at birth (25) and detects bone growth, pubertal bone development and gender differences in the bone development process between 3 and 21 years of age (28,29).…”
Section: Introductionmentioning
confidence: 99%